Wool bale stencils : a design history of New Zealand branding and visual identity 1850-2019 : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy, Massey University, Wellington, New Zealand - O'Sullivan, Annette (Massey University, 2019)
Wool bale stencils have had a ubiquitous presence in New Zealand culture for over 150 years. Originating from sheep brands, marks of station identity were stencilled on bales of wool for export to overseas markets. In time, stencilled marks represented the quality of wool and reputation of the station, and became the visual identity for the station. Following discontinuation in the wool industry, at the beginning of the 1990s stencil plates and derivative stencil letters were used for new forms of visual identity in New Zealand design. This material culture study combines historical contextualisation with close reading of objects, and observes their social life or how they have been used by people over time. It draws on object and visual evidence found on ﬁeld trips to historic New Zealand sheep stations, and examples of how stencils have been used in contemporary culture. The thesis is structured through the life stages of a designed object: design and making; using, consuming, and distributing; and discarding and recycling. This maps the transformations of the wool bale stencil from an everyday utilitarian object to new forms of expression and representation in New Zealand design. Within the overarching theme of branding and identity of people, products, and places, this study of design history reﬂects on the meaning and signiﬁcance of wool bale stencils in New Zealand.
Keywords: Wool baling; New Zealand; History; Stencils and stencil cutting; Branding (Marketing); 330304 Design history, theory and criticism